Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1744-7348.2008.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric evaluation of perennial ryegrass (Lolium perenne) for the prediction of in vitro dry matter digestibility

Abstract: Thermogravimetry (TG) can be used for assessing the compositional differences in grasses that relate to dry matter digestibility (DMD) determined by pepsincellulase assay. This investigation developed regression models for predicting DMD of herbage grass during one growing season using TG results. The calibration samples were obtained from a field trial of eight cultivars and two breeding lines. The harvested materials from five cuts were analysed by TG to identify differences in the combustion patterns within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The use of fiber-rich products, such as agroindustrial by-products, can reduce the cost of feeding animals (Zambom et al 2001). Additionally, Marvin et al (1996) and Sharma et al (2008) reported that thermal analysis gave physical properties associated with quality of ruminant feed. The in vivo evaluation of the nutritive value of feeds through the measurement of feed intake, total tract apparent digestibility and productive performance requires more time and cost as compared with laboratory level experiments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of fiber-rich products, such as agroindustrial by-products, can reduce the cost of feeding animals (Zambom et al 2001). Additionally, Marvin et al (1996) and Sharma et al (2008) reported that thermal analysis gave physical properties associated with quality of ruminant feed. The in vivo evaluation of the nutritive value of feeds through the measurement of feed intake, total tract apparent digestibility and productive performance requires more time and cost as compared with laboratory level experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Reliable estimates of feed quality may be obtained by simple, low-cost laboratory techniques such as in vitro, in situ and chemical methods (Tilley & Terry 1963;Orskov & McDonald 1979). Additionally, Marvin et al (1996) and Sharma et al (2008) reported that thermal analysis gave physical properties associated with quality of ruminant feed. This technique is based on the variation of mass over time or temperature in thermogravimetric analysis (TG) and measurement of heat flow within samples at a set temperature in differential scanning calorimetry analysis (DSC) (Santos et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation